Dampak Alih Usaha Pertanian terhadap Pendapatan Pemilik Lahan di Desa Banua Binjai Kecamatan Pandawan Kabupaten Hulu Sungai Tengah - K Khairunnisa; Lina Suherty (PPJP Universitas Lambung Mangkurat, 2020)
This study aims to explain the agricultural business's impact on the land owner's socio-economic conditions regarding livelihood structure and ownership of agricultural land. A factor affecting land-use change is the lack of workforce to work on or manage agricultural land in Banua Binjai Village.Landowner income before over agricultural business and after over agricultural business changes in the form of an increase. Gain occurs to people in Banua Binjai village over the farming business and is influenced by several factors: lack of labor to work on the land, the family's economic pressure, and the desire to open a new business. Based on paired t-test results, it is known that the t-count of -6.435 with a significance value of 0,000 (p <α). The test results can be concluded that accepting Ha and rejecting Ho means that there is a difference in the income of landowners in Banua Binjai Village between before and after land conversion.